Effect of organic residue compost made from household waste, plant residues and manure on the growth of lettuce (2018)
Composting is an alternative for recycling biodegradable organic solid wastes, turning them into fertilizers for agriculture and avoiding improper disposal in landfills. Thus, the objective of the present study was to evaluate the physical-chemical and microbiological quality of a compound produced from organic residues and its performance in the development and productivity of a crisp lettuce cultivar (Lactuca sativa L.), in greenhouse conditions. For the compost, household waste (food residue) and cattle manure were used at a 1:1 ratio. For the construction of the compost piles, the organic residues were mixed with wood chips. Different concentrations of the mature compost (20, 40, 60, 80, and 100% compost) were evaluated in the lettuce cultivation substrate in a randomized block design, with three replicates. The results showed that the organic compost had physical-chemical and microbiological characteristics within agronomic use patterns that, when added to the coconut fiber substrate, favored lettuce production, promoting a 63% increase in plant height and 75% increase in the number of leaves.